IMPROVING THE CALCULATING SKILLS OF SUBTRACT AND ADDING INTEGER USING BEADING PROVIDERS FOR CLASS VI STATE 3rd ELEMENTARY SCHOOL KUWASEN JEPARA - M. Aham Rozikin (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
This research aims to improve the Mathematics learning outcomes of class VI students using Beads teaching aids in 2023/2024 at SD Negeri 03 Kuwasen, Jepara Regency, Jepara Regency. This classroom action research was carried out in two cycles. The subjects in this research were students in class VI of SD Negeri 03 Kuwasen, Jepara District, Jepara Regency, totaling 18 students. In data collection techniques, test techniques are used, and in data analysis, percentages of learning outcomes between pre-cycle and cycles I, and II are used. The results before the research was carried out were that in the pre-cycle only 5 students or 49% achieved the km, in the first cycle this increased to 6 students who achieved the kkm, or 61%, and in the second period, it increased. A total of 16 students achieved the KKM, namely 76%. This research was successful because it provided more value than the KKM, namely ≥ 76% of all students with KKM≥70. It was concluded that learning with beaded teaching aids can improve learning outcomes in mathematics subjects such as subtracting and adding integers.